1981
DOI: 10.1007/bf00257424
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis of diabetes mellitus in a geographically defined population

Abstract: The centralised registration and care of all diabetics in a geographically defined population has provided an epidemiological basis for a longitudinal investigation of the prognosis of this disease. Records of all newly diagnosed diabetics who had been registered in the Erfurt district (population 1.25 million) in 1966 were studied in relation to the time period 1966-1976. Of the known 2,560 diabetics (910 men, 1,650 women; 93.7% greater than 40 years of age), 1,054 had died during the 10-year follow-up period… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

16
59
1
5

Year Published

1983
1983
2001
2001

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(81 citation statements)
references
References 14 publications
16
59
1
5
Order By: Relevance
“…The high frequency of cerebro-cardiovascular and renal diseases as causes of death in diabetes was also noted in two previous Japanese reports [12,16], and resembles closely findings obtained in studies on diabetic patients in the West [4,6,8,14]. However, the frequency of three major angiopathies in our study somewhat differs from that in the West.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The high frequency of cerebro-cardiovascular and renal diseases as causes of death in diabetes was also noted in two previous Japanese reports [12,16], and resembles closely findings obtained in studies on diabetic patients in the West [4,6,8,14]. However, the frequency of three major angiopathies in our study somewhat differs from that in the West.…”
Section: Discussionsupporting
confidence: 90%
“…The O/E ratios found in our male and female patients correspond to most of those found in studies carfled out in the West [5,7,8]. In our study, a higher mortality was found in diabetic men than in diabetic women, which agrees with some [4,5], but not other studies from Western countries [1,5,7,14].…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…This loss of survival advantage has been noted in other studies for women with diabetes [15,16] and could be due to a relative loss of protection from cardiovascular deaths among women with diabetes [8,17]. This study also found that women with Type I diabetes tended to have a higher excess mortality than men with Type I diabetes.…”
Section: Discussionsupporting
confidence: 85%